Henri Bergson e a questão da linguagem - Silva, Fábio Coelho da (2021)
This research aims to analyze the topic of language in the philosophy of Henri Bergson. More specifically, we seek to explain that the interlacing of different considerations about the topic converges into a malleable and fluid conception of philosophy. We divided the study into three phases. First, we focus on the elaboration of method in philosophy and show the meaning of concept criticism and the appeal to images. Second, we use the Bergsonian interpretation of the evolutionary process to describe the link between intelligence and language in the human interaction with things, or, in other words, the way intelligent signs are decisive in not only defining the scope of actions, but also inaugurating the speculative field. Third, we evaluate the role of language in society life, sometimes acting as an instrument to maintain the “closed societies”, and other times acting as an expression impregnated with emotion that stimulates deep contact between individuals and with humanity as a whole.